2012
DOI: 10.1364/ol.37.001628
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high efficiency multilayer blazed gratings through deposition kinetic control

Abstract: Diffraction efficiency of multilayer coated blazed gratings (MBG) strongly depends on the perfection of the saw-toothshaped layers in the overall composite structure. Growth of multilayers on saw-tooth substrates should be carefully optimized in order to reduce groove profile distortion and at the same time to avoid significant roughening of multilayer interfaces. In this work we report on a new way to optimize growth of sputter-deposited Mo/Si multilayers on saw-tooth substrates through variation of the sputt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…how fast the efficiency decays with deviation from the ideal blazing condition. Our experimental experience in MBG fabrication [1][2][3] indicates that a modest deviation from (1) is not harmful and in many cases can be tolerated. Another question raised by Underwood et al, [7] is how refraction of x-rays in multilayer media affects the blazing condition.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…how fast the efficiency decays with deviation from the ideal blazing condition. Our experimental experience in MBG fabrication [1][2][3] indicates that a modest deviation from (1) is not harmful and in many cases can be tolerated. Another question raised by Underwood et al, [7] is how refraction of x-rays in multilayer media affects the blazing condition.…”
mentioning
confidence: 88%
“…Recent progress in the technology of multilayercoated blazed gratings (MBG) [1][2][3] opens important opportunities for the development of a new generation of spectrometers for EUV and soft x-rays [4,5]. The gratings have superior efficiency characteristics over lamellar gratings due to their blazing ability, which is provided by the slanted facets of the sawtooth grooves.…”
mentioning
confidence: 99%
“…A comparison of calculated with measured reflection coefficients of a multilayer mirror (witness) revealed that the parameters À Zr = 0.4 and Á = 10.43 nm, incorporated in a model of multilayer Al/Zr grating coating, correlate well with the growth values and that the average interface roughness can be defined by ' 0.9 nm ( 0 ' 0.4 nm, 0 = 10 nm) (Voronov, Gawlitza et al, 2012;Voronov, Anderson et al, 2012). The data obtained in this comparison argue for $90% TE-polarized incident radiation (intensity).…”
Section: Al/zr Gratingmentioning
confidence: 99%
“…Diffraction gratings on blazed-profile Si substrates are fabricated by interference or electron lithography and selective etching in KOH of Si plates cut at an angle ' (Voronov et al, 2010;Voronov, Anderson, Cambie, Cabrini et al, 2011;Voronov, Gawlitza et al, 2012;Voronov, Anderson et al, 2012). While fabrication of gratings of a large size with d 200 nm for the short-wave range shows considerable promise, realization of the available design potential requires that the relevant technology produces a grating profile close to the ideal triangular geometry and coatings made up of tens or hundreds of atomic layers with subatomically smooth boundaries.…”
Section: Simulation Of the Multilayer Grating Boundary Growth And Of mentioning
confidence: 99%
“…[116][117][118] Voronov et al have made significant development in high groove density (small period) MBGs. [119][120][121][122][123] A record of 52% diffraction efficiency at k ¼ 13.4 nm was achieved using the 2nd order of a Mo/Si coated MBG with a groove density of 2525 lines/mm ( Figure 9). 121 A 10 000 line/mm MBG with 13.2% efficiency at normal incidence was demonstrated at k ¼ 19.2 nm.…”
Section: Multilayer Coated Gratingsmentioning
confidence: 99%